Neural dysfunction during temporal discounting in paediatric Attention-Deficit/Hyperactivity Disorder and Obsessive-Compulsive Disorder. (30th November 2017) - Norman, Luke J.; Carlisi, Christina O.; Christakou, Anastasia; Chantiluke, Kaylita; Murphy, Clodagh; Simmons, Andrew; Giampietro, Vincent; Brammer, Michael; Mataix-Cols, David; Rubia, Katya
Abstract: Both Attention-Deficit/Hyperactivity Disorder (ADHD) and Obsessive-Compulsive Disorder (OCD) are associated with choice impulsivity, i.e. the tendency to prefer smaller immediate rewards over larger delayed rewards. However, the extent to which this impulsivity is mediated by shared or distinct underlying neural mechanisms is unclear. Twenty-six boys with ADHD, 20 boys with OCD and 20 matched controls (aged 12–18) completed an fMRI version of an individually adjusted temporal discounting (TD) task which requires choosing between a variable amount of money now or £100 in one week, one month or one year. Activations to immediate and delayed reward choices were compared between groups using a three-way ANCOVA. ADHD patients had steeper discounting rates on the task relative to controls. OCD patients did not differ from controls or patients with ADHD. Patients with ADHD and OCD showed predominantly shared activation deficits during TD in fronto-striato-insular-cerebellar regions responsible for self-control and temporal foresight, suggesting that choice impulsivity is mediated by overlapping neural dysfunctions in both disorders. OCD patients alone showed dysfunction relative to controls in right orbitofrontal and rostrolateral prefrontal cortex, extending previous findings of abnormalities in these regions in OCD to the domain of choice impulsiveness. Highlights: ADHD patients alone showed significantly steeper discounting relative to controls. ADHD and OCD shared underactivation in fronto-striato-insular-cerebellar regions during delayed choices. Only patients with OCD had dysfunction in right orbitofrontal and rostrolateral prefrontal cortex relative to controls.